1990
DOI: 10.2307/976784
|View full text |Cite
|
Sign up to set email alerts
|

Management Information Systems in Public and Private Organizations: An Empirical Test

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
163
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(206 citation statements)
references
References 10 publications
5
163
0
8
Order By: Relevance
“…Assim, modelos de gestão são aplicados no setor privado. Apesar disso, essa adequação de modelos de gestão não é trivial e deve levar em consideração as características inerentes ao setor público, diferentes das do setor privado (Bretschneider, 1990;Torres, 1997). Com isso, um dos focos de ação dos governos contemporâneos tem sido a elaboração de políticas públicas eficazes que supram as necessidades individuais, institucionais e regionais da sociedade, promovendo o desenvolvimento social e econômico (Barbosa Filho, 2000).…”
Section: O Governo Eletrônico No Setor Público Brasileirounclassified
“…Assim, modelos de gestão são aplicados no setor privado. Apesar disso, essa adequação de modelos de gestão não é trivial e deve levar em consideração as características inerentes ao setor público, diferentes das do setor privado (Bretschneider, 1990;Torres, 1997). Com isso, um dos focos de ação dos governos contemporâneos tem sido a elaboração de políticas públicas eficazes que supram as necessidades individuais, institucionais e regionais da sociedade, promovendo o desenvolvimento social e econômico (Barbosa Filho, 2000).…”
Section: O Governo Eletrônico No Setor Público Brasileirounclassified
“…São muitos os autores que analisaram a interdependência organizacional, a externalidade e o elevado número de steakeholders em conflito na dinâmica interna e externa da administração pública (Bretschneider 1990 Quais as consequências do processo de mútua influência? Estas perguntas conduzem-nos à teoria dos steakeholders, que tem vindo a crescer em importância nos últimos trinta anos (Freeman, 1984;Alkhafaji, 1989;Goodpaster, 1991;Harrison & Freeman, 1999;Donaldson & Preston, 1995;Jones, 1995;Clarkson, 1994;1995;Wood, 1994;Carrol, 1979;1993, citados por Smith, 2008 e acaba por constituir um dos pontos de partida no estudo do egovernment, dada a necessidade de envolvimento de numerosos organismos na conceção e realização de projetos orientados aos eventos de vida.…”
Section: A Coordenação Horizontal E Sistémica Na Administração Públicaunclassified
“…Bretschneider (1990) describes this phenomenon as the higher level of "red tape" experienced by public sector organizations.…”
Section: Public and Private Sector Organizationsmentioning
confidence: 99%
“…During the 1990s, researchers began to distinguish between management information systems (MIS) designed for public (government) and private sector organizations (Bretschneider, 1990;Cats-Baril & Thompson, 1995;Caudle, 1990;Newcomer & Caudle, 1991). Bretschneider (1990) studied public management information systems (PMIS) and suggested that they varied from MIS systems in private enterprises. He identified several differences in managing information systems between the public and private sectors.…”
Section: Public and Private Sector Organizationsmentioning
confidence: 99%